An investigation of water usage in casual dining restaurants in Kansas - VanSchenkhof, Matthew (Kansas State University, 2011)
Hospitality operations are considered the heaviest consumers of energy and water per square foot of building space among commercial industries. Water and its processing may make up more than 80% of hospitality operations’ utility costs, and will continue to increase due to infrastructure upkeep, higher demand, and climate change effects. Implementing water efficiency in Kansas restaurants could save two billion gallons of water each year. Studying the current water usage in Kansas restaurants may result in decreased costs, increased awareness and more sustainable water use. The purposes of this study are to (1) identify water usage via metrics employing water and sales data from a sample of Kansas’ casual dining restaurants (CDR’s) and (2) determine whether the antecedents of behavioral intent can predict owner intent to reduce water use using the Theory of Planned Behavior (TpB). Objectives include: 1. Establish how much water is currently used across multiple metrics in CDR’s. 2. Understand differences of water use metrics in CDR’s between location, type of food, type of ownership, kitchen equipment, and revenues. 3. Using TpB, ascertain owner’s intent to decrease water usage.
Keywords: Water Usage; Restaurants